Performa pertumbuhan bawal bintang Trachinotus blochii yang dibudidaya dengan sistem monokultur dan polikultur bersama kerang hijau Perna viridis - Kurnopriawan Hidayat; Herman Yulianto; Mahrus Ali; Nuning Mahmudah Noor; Berta Putri (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2019)
Abstract. The snubnose pompano Trachinotus blochii is one of the important commercial fishery commodity in the Indonesian market. The increasing of the market demand has led some efforts to increase the production of this fish. So do the increasing need for green mussels Perna viridis meat. Therefore it is necessary to evaluate the performance of both species in the polyculture system by using raft culture. This study aims to compare the growth performance of snubnose pompano cultivated on a monoculture system and polyculture within green mussels in a raft system. The parameter observed was the differences in the growth performance of both species and the increase in total weight and survival (SR) of the fish. The results showed that the growth of snubnose pompano did not provide a significant difference in the growth of both cultivating systems whether in monoculture or polyculture system, likewise the shell length and width of the green mussels. We conclude that it is profitable to cultivate both organisms on a polyculture system because it can harvest both green mussels and snubnose pompano together in a period.Keywords: Snubnose pompano, green mussel, monoculture, polyculture, raft, growthAbstrak. Permintaan pasar terhadap daging ikan bawal bintang semakin meningkat begitupun dengan daging kerang hijau sehingga diperlukan suatu upaya rekayasa teknologi budidaya. Salah satunya adalah dengan menerapkan sistem polikultur dalam keramba jaring apung. Penelitian ini bertujuan membandingkan faktor pertumbuhan ikan bawal bintang dan kerang hijau yang dibudidayakan dengan sistem monokultur dan polikultur. Pengamatan dilakukan pada perbedaan pertumbuhan ikan dan kerang hijau, juga pada mutlak serta survival rate (SR). Hasil penelitian menunjukkan bahwa pertumbuhan panjang dan lebar bawal bintang tidak memberikan perbedaan pertumbuhan secara nyata baik pada perlakuan monokultur dan polikultur. Begitupun dengan pertumbuhan kerang hijau sehingga sistem polikultur lebih menguntungkan untuk dilakukan karena bisa memanen kerang hijau dan ikan bawal bintang sekaligus.Kata Kunci: kerang hijau, ikan bawal bintang, monokutur, polikultur, pertumbuhan, KJA.